1971
DOI: 10.3758/bf03212627
|View full text |Cite
|
Sign up to set email alerts
|

Infant responses to approaching objects: An indicator of response to distal variables

Abstract: Infants show an adaptive avoidance response to approaching objects. The response is affected by the closeness and speed of approach. It is mediated by visual variables. Air-pressure changes do not elicit the response. This kind of response implies discrimination and response to distal variables rather than merely to their proximal mediators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
49
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(53 citation statements)
references
References 3 publications
(4 reference statements)
1
49
0
Order By: Relevance
“…It is some time since Yonas (Yonas & Pick, 1975) first announced that the defensive responses to approaching objects reported by Bower, Broughton, and Moore (1971) and Ball and Tronick (1971) were in fact postural changes produced by tracking of the top contour of a display. The claim at the time was intriguing enough that I was moved to have some control experiments performed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is some time since Yonas (Yonas & Pick, 1975) first announced that the defensive responses to approaching objects reported by Bower, Broughton, and Moore (1971) and Ball and Tronick (1971) were in fact postural changes produced by tracking of the top contour of a display. The claim at the time was intriguing enough that I was moved to have some control experiments performed.…”
mentioning
confidence: 99%
“…This has always seemed to me the best explanation for the delay in visual placing (Walters & Walk, Note 1). Bower et al (1971) and Ball and Tronick (1971) did not have parents holding the babies. Ball and Tronick did have some support, presumably purely to prevent lateral movement, since the babies were on a baby seat.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, motion perspective specifies the rate of approach of an object, time to collision with an object, and path of approach of an object relative to a stationary organism. Gibson (1958) has argued that such information is of crucial importance in the behavioral ecology of an organism since it provides the animal with a basis for capturing food, avoiding a predator, and locomoting around obstacles.Many investigators (Ball & Tronick, 1971;Bower, Broughton, & Moore, 1971 ; Schiff, 1965; rronick, 1967) have demonstrated that optical information which specifies a looming object is used by human infants, chicks, rhesus infants, frogs, and crabs to avoid impending collision. The pickup of this information is specific enough to allow these animals to distinguish between a receding object, an approaching object on a collision course, and an approaching object on a noncollision course.…”
mentioning
confidence: 99%
“…Many investigators (Ball & Tronick, 1971;Bower, Broughton, & Moore, 1971 ;Schiff, 1965;rronick, 1967) have demonstrated that optical information which specifies a looming object is used by human infants, chicks, rhesus infants, frogs, and crabs to avoid impending collision. The pickup of this information is specific enough to allow these animals to distinguish between a receding object, an approaching object on a collision course, and an approaching object on a noncollision course.…”
mentioning
confidence: 99%